Traffic and λ grooming. - Cinkler, T.
The article gives an overview of traffic grooming and lambda grooming in multilayer networks, and discusses the advantages and drawbacks of these methods as well as applications and future alternative directions.
Keywords: WDM networks; Future directions; Lambda grooming; Multilayer networks; Traffic grooming